Lessons Learned - Amanda Phelan BNS, MSc, PhD; Michaela Davis BNS, MSc PhD (SAGE Publishing, 2015)
The public health nurses' scope of practice explicitly includes child protection within their role, which places them in a prime position to identify child protection concerns. This role compliments that of other professions and voluntary agenices who work with children. Public health nurses are in a privileged position as they form a relationship with the child's parent(s)/guardian(s) and are able to see the child in its own environment, which many professionals cannot. Child protection in Ireland, while influenced by other countries, has progressed through a distinct pathway that streamlined protocols and procedures. However, despite the above serious failures have occurred in the Irish system, and inquiries over the past 20 years persistently present similar contributing factors, namely, the lack of standardized and comprehensive service responses. Moreover, poor practice is compounded by the lack of recognition of the various interactional processes taking place within and between the different agencies of child protection, leading to psychological barriers in communication. This article will explore the lessons learned for public health nurses practice in safeguarding children in the Republic of Ireland.